2016
DOI: 10.3171/2015.6.peds1562
|View full text |Cite
|
Sign up to set email alerts
|

Allograft versus autograft for pediatric posterior cervical and occipito-cervical fusion: a systematic review of factors affecting fusion rates

Abstract: OBJECT Fusion rates are high for children undergoing posterior cervical fusion (PCF) and occipito-cervical fusion (OCF). Autologous bone has been widely used as the graft material of choice, despite the risk of donor-site morbidity associated with harvesting the bone, possibly because very low fusion rates were reported with posterior allograft cervical fusions in children several decades ago. Higher overall fusion rates using allograft in adults, associated with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…However, in a subgroup analysis for rigid internal fixation techniques including only 18 patients from 5 different studies where allograft was used, the differences were smaller (99% vs 94%, respectively). [19] In an adult population, Godzik and colleagues reported in adult population bony OC fusion in allograft group in 18 of 19 (95%) and 8 of 8 (100%) in the autograft group after a minimum of 12-month follow-up. [8] To overcome the lack of osteoinductive function of allograft, the use of bone marrow aspirate (BMA) [15] or bone morphogenetic proteins (BMP) are advocated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a subgroup analysis for rigid internal fixation techniques including only 18 patients from 5 different studies where allograft was used, the differences were smaller (99% vs 94%, respectively). [19] In an adult population, Godzik and colleagues reported in adult population bony OC fusion in allograft group in 18 of 19 (95%) and 8 of 8 (100%) in the autograft group after a minimum of 12-month follow-up. [8] To overcome the lack of osteoinductive function of allograft, the use of bone marrow aspirate (BMA) [15] or bone morphogenetic proteins (BMP) are advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is a challenge to harvest and craft a well-fitting bone block from a small costa or thin iliac crest in children. [8,19,21] Allografts are only osteoconductive, weakly osteoinductive, but not osteogenic like autografts; therefore, their use in posterior fixation is associated with a higher rate of nonunion. [4] An older publication by Koop et al (1984) noted that pseudoarthrosis occurred in one patient who received allograft instead of autograft in their pediatric OC fusion procedures, strengthening this author's view that autograft is superior in fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [12] compared the fusion rate between autograft and allograft for pediatric patients with AAF, reporting that 94% of the fusion rates with allograft was comparable with 100% of the fusion rate with autograft. However, Reintjes et al [9] reported 80% rate of bony fusion with allograft and 94% bony fusion with autograft. The advantages of autogenic bone are the low cost and reduced potential risk of viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, screw placement may be technically difficult in very young children because of small bone size, congenital variations, possible growth potential, and immature ossification [7,8]. With regard to bone grafts, autogenic iliac crest bone has long been considered the ‘gold standard’ bone source for posterior cervical fusion in pediatric patients [5,9,10]. However, there are some unsolved problems associated with donor-site morbidity and amount of bone grafting.…”
Section: Introductionmentioning
confidence: 99%